Tribal Demography in Thiruvannamalai District of Tamil Nadu – A Study - Manikandan, B; Karthikeyan, B (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
Thiruvannamalai is one of the world famous cities as it has the strong traditional heritage from the past. The physical features of Thiruvannamalai turn the attention of the people from the various direction of the world.  It is considered as the heart of the world. It is the abode of the all souls and it is the place where physical share of the Lord Siva to Parvathi and so it is the place of the spiritual centre. Thiruvannamalai district has many glorious attributes such as fertile topography, tourist locations, various spiritual centers for edification of the mind and life system, festivals which are symbols of the cultural activities of the people, forest resources, water resources for fertile land and agriculture, many hill traces of the Eastern Ghats and Jawadhu hills which is abode of the tribes and a good administrative set up.  The demography is the most important tool for any country for gauging level of the nation. The demography status of national, state and district level have been brought forth in this article. There are eighteen blocks situated in Thiruvannamalai district of Tamil Nadu and there are 860 villages are located in eighteen blocks in Thiruvannamalai district.  Out of 860 villages, the tribal concentrated villages are only 528 and the remaining villages are non tribal areas. 90.54% of tribes are living in Jawadhu Hills block and it is the maximum tribal concentrated area in this district.  Next to Jawadhu Hills, Thandrampattu has secured 9.52% of tribes are living and placed in second in this district.  The total number of the tribes in this district is 87096. Out of it, number of male tribe is 44021 and female tribe is 43075 and so the sex ratio of the tribe in this district more or less equal with small variation.  The total tribal percentage while comparing with other people is 4.27%.  Notwithstanding the quantity of the tribal people in this district is low,  it is unavoidable to concentrate on it.
Keywords: Traditional; Heritage; Spiritual; Demography; Glorious; Fertile; Topography Edification; Jawadhu Hills; Concentration and Variation